Central Bank Financial Strength and Monetary Policy Effectiveness: Institutional and Governance Perspectives from a Systematic Literature Review - Mega Fauziah; Hermanto Siregar; Solikin M. Juhro; Tanti Novianti; Mega Fauziah; Hermanto Siregar; Solikin M. Juhro; Tanti Novianti (Bank Indonesia, 2026)
The study offers an interpretation of how central bank financial strength is constructed through legal and governance frameworks by systematically reviewing 17 scholarly articles. Based on the findings of this systematic literature review, it is evident that central bank financial strength is influenced by various legal frameworks, such as capitalisation rules, loss-absorption rules, surplus distribution rules, and a legal framework that outlines the relationship between monetary and fiscal authorities. The findings suggest that insufficient Central Bank Financial Strength (CBFS) can lead to governance issues, such as greater fiscal dependence and reduced protection against political interference. The review identifies important institutional and legal implications. The study concludes that it is crucial to strengthen capital adequacy rules, ensure transparent reporting, establish independent oversight, and have clear procedures for recapitalisation. From this perspective, it is evident that CBFS is part of the legal framework of central banking and offers a design-based platform through which central banking authorities can build and maintain credibility.